Widespread compact fluorescent lamp evaluations in 50 Hz electrical network - Ruhaizad Ishak; Ahmad Syahiman Mohd Shah; Mohd Ikhwan Muhammad Ridzuan; Noraslinda Muhamad Bunnori (Bulletin of Electrical Engineering and Informatics, 2023)
Rapid development in electrical technology has imposed strong challenges to modern power system. Power quality has become a great concern due to proliferation of power electronic technology in modern electrical loads. Specifically for lighting load such as compact fluorescent lamps (CFLs), one of the concerning issues is harmonics. CFL is a cost-competitive and energy efficient compared to incandescent lamp. Inevitably, CFL produces harmonics current due to nonlinearity behaviour of the electronic ballast circuit. This paper presents a study on the widespread installation of CFL lamps in electrical power network. Initially, the harmonic current characteristics of local-branded CFL was identified from laboratory measurement. Then, a simulated CFL model was developed in MATLAB/Simulink to replicate the identified characteristics. The same step was repeated for other two different brands where eventually all models were embedded into a distribution network. The results show that at low voltage level, with installation more than 50 units for each type of CFL, the harmonic voltage distortion exceeded the 8% total harmonic distortion (THD) limit as stipulated in EN50160 standard. However, at higher voltage, the amount of THD decreased to average 0.94% and further down to average 0.28% at small transmission voltage level.